One-pot thermal evaporation synthesis of CdS-RGO hetrostructure and its field emission study - Bansode, Sanjeewani R.; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
CdS-RGO heterostructure was synthesized by thermal evaporation method. The as-synthesized CdS-RGO heterostructure was characterized using X-ray Diffraction, SEM, and EADX, before field emission (FE) studies. The FE characteristics of a planar emitter made up of as-synthesized CdS-RGO heterostructures were measured at the base pressure 1x10(-8) mbar. The synthesized CdS-RGO heterostructure emitter is found to deliver a current density similar to 70 mu A/cm(2) at an applied electric field of similar to 4.7 V/mu m. Moreover, the nanocomposite shows excellent emission stability without significant current degradation making CdS-RGO heterostructure as a promising electron source for practical applications in various vacuum nano-microelectronic devices.